Study Microstructure of Fe3O4 Modification Using PEG 4000 form Iron Sand at Wari Ino Beach As A Biosensor Application - Kurnia, Kurnia; Kaseside, Meidy; Iwamony, Steven (Indonesian Journal of Chemical Research, 2021)
Fe3O4 encapsulated PEG form iron sand at wari ino beach has been successfully synthesized by co-precipitation method. The average particle size of the nanoparticle 11,3 nm was determined by scherrer formula. Fe3O4 modification PEG 4000 was successfully encapsulated the samples by the presence C-O-C and CH bonding that were characterized using Fourier Transform Infra Red (FTIR), X-Ray Diffraction (XRD) pattern shows that all samples are formed by single phase cubic spinel magnetite , and Scanning Electron Microscopy (SEM) shows the high dispersion capability while encapsulated process using PEG. The results of the characterization show that the Fe3O4 successfully encapsulated by PEG 4000.